Gender-age and socio-demographic risk factors for non-psychotic mental disorders in individuals with aseptic necrosis of the femoral head - Ogorenko Вікторія; Shornikov Андрій (Psychosomatic Medicine and General Practice, 2022)
Background. The presence of chronic pain in the structure of hip avascular necrosis hurts the patient’s mental state, causes chronic postoperative pain, and reduces the quality of life. Treatment of nonpsychotic mental disorders may be a therapeutic strategy to reduce risk factors for health-related quality of life and satisfaction with treatment outcomes. Successful rehabilitation of patients with hip avascular necrosis consists of restoring the functions of the affected joints and providing the necessary psychological assistance, through the available nonpsychotic mental disorders and gender-age features. The study aimed to determine the gender age and socio-demographic characteristics of patients with aseptic necrosis of the femoral head, which may act as predictors of the risk of developing non-psychotic mental disorders. Methods. 137 persons with aseptic necrosis of the femoral head were examined: 92 (67.2%) men and 45 (32.8%) women, the average age was 52.01 ± 11.29 years. In addition to the clinical-psychopathological and socio-demographic examination were used the Beck depression inventory, the Beck anxiety inventory and Teilor’s Manifest Anxiety Scale, the Beck hopelessness scale, and the Toronto alexithymia scale (TAS-20) were. Results. It was found that 25.8% (17/66) of people with higher education were engaged mainly in manual labour, but at the time of the survey, only 7.6% (5/66) were working. It was found that there is no difference in the levels of depression prevalence depending on gender and age. Anxiety levels at a young age are higher in females, but gender and age differences in the prevalence of anxiety levels have not been identified. Among the examined patients, a high level of alexithymia was found in all age and gender groups. There is a tendency for a higher level of hopelessness in young females compared to males.